Endoscopic side-by-side uncovered self-expandable metal stent placement for malignant hilar biliary obstruction. (May 2019) - Kitamura, Katsuya; Yamamiya, Akira; Ishii, Yu; Mitsui, Yuta; Yoshida, Hitoshi
Aim: To investigate outcomes of endoscopic bilateral side-by-side placement across the papilla using 10-mm-diameter uncovered self-expandable metal stents for unresectable malignant hilar biliary obstruction. Methods: We retrospectively analyzed 23 patients who underwent endoscopic biliary uncovered self-expandable metal stent placement for unresectable malignant hilar biliary obstruction between January 2015 and September 2016 at our institution. We performed endoscopic side-by-side placement across the papilla using 10-mm-diameter longer-model uncovered self-expandable metal stents. Outcomes included the technical and functional success rates, recurrent biliary obstruction rate, time to recurrent biliary obstruction, reintervention rate, and incidence of adverse events other than recurrent biliary obstruction. Results: Of the 23 patients, 10 with malignant hilar biliary obstruction underwent endoscopic side-by-side uncovered self-expandable metal stent placement across the papilla (median age, 83 years; 6 men). The locations of malignant hilar biliary obstruction were Bismuth types II ( n = 3), III ( n = 3), and IV ( n = 4). The median common bile duct diameter was 8 mm. The technical and functional success rates were 100% and 80%, respectively. Seven patients (70%) developed recurrent biliary obstruction because of stent occlusions, including early hemobilia in two patients and late tumor ingrowth in five patients. The median time to recurrent biliary obstruction was 66 (95% confidence interval: 29–483) days. Six patients (60%) required reintervention, and 1 (10%) underwent transcatheter arterial embolization for right hepatic arterial pseudoaneurysm. Early adverse events other than recurrent biliary obstruction occurred in four patients and late adverse event in one patient. Conclusion: Endoscopic side-by-side placement across the papilla using 10-mm-diameter uncovered self-expandable metal stents was technically feasible for unresectable malignant hilar biliary obstruction; however, it might be better to avoid this method for patients with malignant hilar biliary obstruction because of high recurrent biliary obstruction rate and shorter time to recurrent biliary obstruction.